Gallstone Dissolution Effects of Combination Therapy with n-3 Polyunsaturated Fatty Acids and Ursodeoxycholic Acid: A Randomized, Prospective, Preliminary Clinical Trial - See Young Lee; Sung Ill Jang; Jae Hee Cho; Min Young Do; Su Yeon Lee; Arong Choi; Hye Sun Lee; Juyeon Yang; Dong Ki Lee (Gut and Liver)
Background/Aims: Ursodeoxycholic acid (UDCA) is the only well-established and widely used agent for dissolving gallstones. Epidemiological and animal studies have suggested potential therapeutic benefits of n-3 polyunsaturated fatty acids (PUFA) for dissolving cholesterol gallstones. We evaluated whether adding PUFA to UDCA improves gallstone dissolution in patients with cholesterol gallstones. Methods: This randomized, prospective, preliminary clinical trial compared the efficacy and safety of UDCA plus PUFA combination therapy (combination group) with those of UDCA monotherapy (monotherapy group). The inclusion criteria were a gallstone diameter ≤15 mm on ultrasonography, radiolucent stones on plain X-ray, and no to mild symptoms. Gallstone dissolution rates, response rates, and adverse events were evaluated. Results: Of the 59 screened patients, 45 patients completed treatment (24 and 21 in the monotherapy and combination groups, respectively). The gallstone dissolution rate tended to be higher in the combination group than in the monotherapy group (45.7% vs 9.9%, p=0.070). The radiological response rate was also significantly higher in the combination group (90.5% vs 41.7%, p=0.007). In both groups, dissolution and response rates were higher in patients with gallbladder sludge than in those with distinct stones. Four adverse events (two in each group) were observed, none of which were study drug-related or led to drug discontinuation. The incidence of these adverse events was similar in both groups (combination vs monotherapy: 9.5% vs 8.3%, p=0.890). Conclusions: UDCA plus PUFA therapy dissolves cholesterol gallstones more effectively than UDCA monotherapy, without significant complications. Further prospective, large-scale studies of this combination therapy are warranted.